2021
DOI: 10.51847/1hp2oqd3zk
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infections in Solid Tumor Malignancy: Risk Factors and Clinical Outcome

Abstract: Bloodstream infection (BSI) is a common complication in patients with solid tumor malignancies but available information on risk factors associated with BSI among these patients is scarce. To determine the associated risk factors and clinical outcomes of antibiotic treatment in BSI solid tumor malignancies. This was a retrospective case-control study performed in the National Care Centre. Adult patients with solid tumor malignancy and positive for blood culture bacteria growth (n=130) as well as adult patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[5] It has a gritty and chalky cut surface due to calcification. [6] Chondroblastoma presenting on the distal phalanx of the great toe was unusual. Several studies have concluded that CB is derived from epiphyseal cartilage cells or in the adult population it may be due to chondroid formation by multipotential mesenchymal cells of tendon sheath as suggested by Brien et al [7] Other mimics like giant cell tumors, chondromyxoid fibroma, aneurysmal bone cysts, and clear cell chondrosarcoma were differentiated on a histopathological examination.…”
Section: Resultsmentioning
confidence: 99%
“…[5] It has a gritty and chalky cut surface due to calcification. [6] Chondroblastoma presenting on the distal phalanx of the great toe was unusual. Several studies have concluded that CB is derived from epiphyseal cartilage cells or in the adult population it may be due to chondroid formation by multipotential mesenchymal cells of tendon sheath as suggested by Brien et al [7] Other mimics like giant cell tumors, chondromyxoid fibroma, aneurysmal bone cysts, and clear cell chondrosarcoma were differentiated on a histopathological examination.…”
Section: Resultsmentioning
confidence: 99%
“…The level of plasma lipid peroxidation was assessed in the course of determining the active substances contained in plasma using a kit manufactured by Agat-Med (Russia) and by the content of acyl hydroperoxides in plasma (Ashtiani et al, 2021;Ong et al, 2021). In all cases, the level of plasma antioxidant activity was determined (Abdaltif et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Accumulation of clofazimine in macrophages likely affects the capacity of macrophages to process and present antigens thereby limiting their movement and activation, IL-2 release, and clonal expansion. In contrast to dapsone, this drug has a role in suppressing the release of cytokines (IL-1) causing decreased movement of lymphocytes to the type 1 reaction site or reversal reaction [19]. Due to the long half-life of this drug (about 2 months) and its tissue storage, it can maintain activity even when given intermittently, although intermittent administration is not as effective as regular daily administration or when given intermittently every 2 days.…”
Section: Chlofaziminementioning
confidence: 99%